Modos de vida y consumo de energizantes en los estudiantes de la carrera de Enfermería de la Universidad Nacional de Loja - Carrión Jiménez, María Isabel (2022)
Lifestyles are characterized by identifiable behavioral patterns that can have an effect on an individual’s health and relate to various aspects that reflect attitudes, values and behaviors in a person’s life. This research study was carried out to analyze the relationship between lifestyle and energy-drinks consumption in students of the Nursing career at the Universidad Nacional de Loja for the strengthening of healthy lifestyles. This was a descriptive, quantitative, cross-sectional study. The universe was made up of 91 students who were applied the "Fantastic" Test previously validated by the Health Ministry of Canada that evaluated lifestyles and for the consumption of energy-drinks it was taken the questionnaire of the study Chicaiza & Rubio 2019. The data were analyzed in the statistical program SPSS version 21, the same ones were exposed in tables. The results showed that 71% are female, 80% are in the 20-25 age range, 93% are unmarried, 87% are childless and 91% are not working. In addition, it was identified that there is no relationship between lifestyle and consumption of energy-drinks, and in order to strengthen lifestyles an information brochure was developed with actions aimed at promoting comprehensive health that was delivered to students